Effect of recombinant Human Pentraxin 2 vs placebo on change in forced vital capacity in patients with idiopathic pulmonary fibrosis: a randomized clinical trial - Raghu, Ganesh; Kreuter, Michael (The journal of the American Medical Association, 2018)
Importance Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease with poor prognosis. Approved therapies do not halt disease progression. Objective To determine the effect of recombinant human pentraxin 2 vs placebo on change from baseline to week 28 in mean forced vital capacity (FVC) percentage of predicted value. Design, Setting, and Participants Phase 2, randomized, double-blind, placebo-controlled trial conducted at 18 sites in 7 countries of eligible patients with IPF (N = 117; aged 40-80 years; FVC ≥50% and ≤90% predicted; ratio of forced expiratory volume in the first second/FVC >0.70; diffusing capacity for carbon monoxide [Dlco] ≥25% and ≤90% predicted; and distance of ≥150 m on the 6-minute walk test). Study period was August 2015-May 2017. Interventions Patients were randomized to receive either recombinant human pentraxin 2 (10 mg/kg intravenous every 4 weeks, n = 77) or placebo (n = 39) for 24 weeks, and stratified by concurrent IPF treatment status. Main Outcomes and Measures
Gesehen am 22.05.2020